Pulsatile drug delivery system - Belgamwar, Veena S; Gaikwad, Madhuri V; Patil, Ganesh B; Surana, Sanjay (Asian Journal of Pharmaceutics (AJP), 2014)
Pulsatile drug delivery system is the most interesting time- and site-specific system. This system is designed for chronopharmacotherapy which is based on circadian rhythm. The principle rationale for the use of pulsatile release is for the drugs where a constant drug release, i.e., a zero-order release is not desired. Pulsatile drug delivery system is defined as the rapid and transient release of certain amount of molecules within a short time period immediately after a predetermined off-release period, i.e., lag time. Various systems like capsular systems, osmotic systems, pulsatile system based on the use of soluble or erodible polymer coating, use of rupturable membranes and pulsatile system based on membrane permeability are summarized in this article.These systems are beneficial for the drugs having chronopharmacological behavior where night timeÂ dosing is required and for the drugs having high first-pass effect and having specific site of absorption in gastrointestinal tract.